2016
DOI: 10.1186/s13014-016-0715-6
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient histogram shape analysis for monitoring early response in patients with advanced cervical cancers undergoing concurrent chemo-radiotherapy

Abstract: BackgroundTo explore the role of apparent diffusion coefficient (ADC) histogram shape related parameters in early assessment of treatment response during the concurrent chemo-radiotherapy (CCRT) course of advanced cervical cancers.MethodsThis prospective study was approved by the local ethics committee and informed consent was obtained from all patients. Thirty-two patients with advanced cervical squamous cell carcinomas underwent diffusion weighted magnetic resonance imaging (b values, 0 and 800 s/mm2) before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…With the absence of PTEN, the F p parameter histogram shows a decrease in energy and an increase in entropy value, suggesting that the internal texture features of the tumor are complex. Meng J et al [21] found that as the malignancy of cervical cancer decreases, the ADC entropy value decreases, proving that the entropy value can re ect tumor heterogeneity by re ecting the complexity of the internal texture of the lesion. V e re ects the size of extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…With the absence of PTEN, the F p parameter histogram shows a decrease in energy and an increase in entropy value, suggesting that the internal texture features of the tumor are complex. Meng J et al [21] found that as the malignancy of cervical cancer decreases, the ADC entropy value decreases, proving that the entropy value can re ect tumor heterogeneity by re ecting the complexity of the internal texture of the lesion. V e re ects the size of extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…ADC histogram analysis provides a series of parameters that can reflect tissue heterogeneity and distribution of ADC values based on pixel distribution. ADC histogram analysis has been successfully used for differential diagnosis, histological differentiation, and assessing therapeutic response in various tumors [ 19 22 ]. We detected the dynamic microstructural changes of parotid glands with whole-volume ADC histogram parameters before and after radiotherapy, and assessed if those parameters could predict late xerostomia degrees of NPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Based on histogram analysis of the ROIs, T2 histograms and a variety of parameters were generated through combined analysis by Fire Voxel and SPSS software (version 24, IBM Corp., Armonk, NY, USA). These parameters were divided into two categories 25 , including (1) point-specific parameters, which directly mirrored the T2 values: mean (representing average values within a specific ROI) and other cumulative T2 histograms: lower percentiles (5th, 10th, 25th, 50th) , higher percentiles (75th, 90th, 95th), where the nth percentile was the point EOM involvement evaluation. EOMs were divided into involved or normal-appearing in a binary manner.…”
Section: Methodsmentioning
confidence: 99%
“…Based on histogram analysis of the ROIs, T2 histograms and a variety of parameters were generated through combined analysis by Fire Voxel and SPSS software (version 24, IBM Corp., Armonk, NY, USA). These parameters were divided into two categories 25 , including (1) point-specific parameters, which directly mirrored the T2 values: mean (representing average values within a specific ROI) and other cumulative T2 histograms: lower percentiles (5th, 10th, 25th, 50th) , higher percentiles (75th, 90th, 95th), where the nth percentile was the point at which n percent of voxel values were situated on the left area of the histogram 26 , 27 ; and (2) histogram shape-related parameters, which indirectly reflected the heterogeneous distribution of T2: (a) standard deviation (SD, measuring degree of dispersion from the mean value); (b) skewness (reflecting asymmetry of the histogram distributions); (c) kurtosis (representing the peaked nature of the histogram); (d) entropy (describing irregularity or complexity of the distribution of a parameter of interest); and (e) inhomogeneity (quantifying intralesional heterogeneity).…”
Section: Methodsmentioning
confidence: 99%